2020
DOI: 10.15252/embr.201949898
|View full text |Cite
|
Sign up to set email alerts
|

Aster‐C coordinates with COP I vesicles to regulate lysosomal trafficking and activation of mTORC1

Abstract: Nutrient sensing by the mTOR complex 1 (mTORC1) requires its translocation to the lysosomal membrane. Upon amino acids removal, mTORC1 becomes cytosolic and inactive, yet its precise subcellular localization and the mechanism of inhibition remain elusive. Here, we identified Aster‐C as a negative regulator of mTORC1 signaling. Aster‐C earmarked a special rough ER subdomain where it sequestered mTOR together with the GATOR2 complex to prevent mTORC1 activation during nutrient starvation. Amino acids stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In total, 65 sterol-inspired compounds (Supplementary Figure S4) were synthesised for use in biological screening, featuring 14 distinct secondary heterocyclic scaffolds of which 11 can be classed as pseudo-natural products.Cheminformat- In order to evaluate the suitability of our sterol-inspired library as asource of leads against sterol-transfer proteins,we chose to target the Aster family of CTPs.The Asters (Asters-A, B, and C, also known as GRAMD1A, B, and C respectively) are af amily of sterol transfer proteins responsible for the transport of cholesterol between plasma membranes (PM) and the endoplasmic reticulum (ER). [18] The roles of the Aster proteins in autophagosome biogenesis, [19] lysosomal trafficking and mTORC1 signalling, [20] as well as mitochondrial cholesterol transport [21] have recently been elucidated, however their relevance as drug targets still remains to be determined. Whilst highly selective inhibitors of Aster-A are known, [19] inhibitors of Aster-B and Aster-C have also been identified but suffer from poor selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 65 sterol-inspired compounds (Supplementary Figure S4) were synthesised for use in biological screening, featuring 14 distinct secondary heterocyclic scaffolds of which 11 can be classed as pseudo-natural products.Cheminformat- In order to evaluate the suitability of our sterol-inspired library as asource of leads against sterol-transfer proteins,we chose to target the Aster family of CTPs.The Asters (Asters-A, B, and C, also known as GRAMD1A, B, and C respectively) are af amily of sterol transfer proteins responsible for the transport of cholesterol between plasma membranes (PM) and the endoplasmic reticulum (ER). [18] The roles of the Aster proteins in autophagosome biogenesis, [19] lysosomal trafficking and mTORC1 signalling, [20] as well as mitochondrial cholesterol transport [21] have recently been elucidated, however their relevance as drug targets still remains to be determined. Whilst highly selective inhibitors of Aster-A are known, [19] inhibitors of Aster-B and Aster-C have also been identified but suffer from poor selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Arf1, a GTPase required for COPI vesicle assembly, has recently been implicated in making connections to the ER with other organelles, including lipid droplets and mitochondria [ 16 ]. We have recently shown that Aster-C directly interacts with COPI [ 22 ]. Since the MTS is required for tethering Aster-B between the ER and mitochondria [ 23 ], we first analyzed the interaction between Aster-B and Arf1 by Co-IP analysis in 293A cells transiently expressing GFP tagged Aster-B.…”
Section: Resultsmentioning
confidence: 99%
“…In mechanistic work, the increased lifespan under dietary restriction has been attributed to the benefits of reduced dietary protein, which enhances proteome maintenance via reduced TOR signalling ( Harrison et al, 2009 ; Partridge et al, 2011 ; Kapahi et al, 2017 ; Piper et al, 2017 ; Sabatini, 2017 ; Dobson et al, 2018 ; Liu and Sabatini, 2020 ). Interestingly, lysosomal cholesterol levels have recently been found to be a potent modifier of mTORC1 activity ( Castellano et al, 2017 ; Zhang et al, 2020 ), which raises the possibility that both protein depletion and cholesterol addition modify ageing by reducing TOR signalling. However, the published data shows that cholesterol is an activator of TOR and cholesterol depletion inhibits its activity.…”
Section: Discussionmentioning
confidence: 99%